2013
DOI: 10.5946/ce.2013.46.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Peroral Endoscopic Myotomy for Treatment of Achalasia: Initial Results of a Korean Study

Abstract: Background/AimsAchalasia is a rare esophageal motility disorder. Recently, a novel endoscopic technique, peroral endoscopic myotomy (POEM), was introduced as an alternative treatment for achalasia. We report the results and short term outcomes of POEM for patients with achalasia.MethodsPOEM was performed in 13 patients with achalasia. The procedure consisted of creating a submucosal tunnel followed by endoscopic myotomy of circular muscle bundles. The mucosal entry was closed by conventional hemostatic clips. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 21 publications
1
30
0
5
Order By: Relevance
“…18,19 Recently developed POEM is also effective in lowering LES pressure, but requires longer follow-up and needs to be compared with PD or surgical myotomy. 17,[20][21][22] The most popular protocol of PD is a graded dilatation starting with a 3.0 cm, followed by 3.5 cm and then 4.0 cm balloon, in subsequent sessions balloon. 23 In our institution, a single dilatation with a 3.0 cm balloon is performed as the initial treatment and additional PD is performed according to an "on demand" strategy, based on symptom recurrence during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Recently developed POEM is also effective in lowering LES pressure, but requires longer follow-up and needs to be compared with PD or surgical myotomy. 17,[20][21][22] The most popular protocol of PD is a graded dilatation starting with a 3.0 cm, followed by 3.5 cm and then 4.0 cm balloon, in subsequent sessions balloon. 23 In our institution, a single dilatation with a 3.0 cm balloon is performed as the initial treatment and additional PD is performed according to an "on demand" strategy, based on symptom recurrence during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,[17][18][19][20][21][22][23][24] Previous studies demonstrated that the long-term benefits of surgical and endoscopic treatment of achalasia are directly related with the reduction of the basal LOS pressure. 4,5 Recurrences of dysphagia have been observed more frequently in case of LOS pressure !10 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…The new technique gained a wide popularity and has been enthusiastically embraced by the medical community (especially by interventional gastroenterologists with experience in operative oesophago-gastric endoscopy). As it is often seen when a new technique is introduced the potential for publication bias is at its greatest, and the early reports on POEM were extremely optimistic with almost no complications, rapid recovery and a good-result rate approaching 100% of treated patients (11)(12)(13)(14).…”
mentioning
confidence: 99%